Analysis of Innovation Activity of Enterprises in Modern Business Environment - AKHMETSHIN, Elvir; DANCHIKOV, Evgeniy; POLYANSKAYA, Tatyana; PLASKOVA, Nataliya; PRODANOVA, Natalia; ZHILTSOV, Sergey (Journal of Advanced Research in Law and Economics, 2018)
The article discusses the question of the possibility of the business community to implement mechanisms for the development of its structure. The authors show that in the process of historical transformation are implemented opportunities for market entry and process of improvement activities. The authors show that every company can produce a range of innovative products and its innovative principles transform of striving for improvement in the need to innovate. The subject of research is itself innovative activity of the organization, and the possibility of its integration in market conditions. The novelty of this study is the assumption that the innovation activity of the enterprise does not depend on the amount of goods produced and the number of shipped innovative products. The main indicator is the amount of revenue from goods that are produced on the basis of a new technological cycle. In the course of the work are analyzed the statistics and formed the algorithmization of actions to increase the share of innovative products The authors show and this is the basis for further research that the advancement and increase of the share of innovative products determines the possibility of development of a qualitatively new setting and identifies opportunities for technological and, consequently, the social capital of a certain territory.